Cystic fibrosis newborn screening: the importance of bloodspot sample quality. Issue 3 (28th August 2020) - Doull, Iolo; Course, Christopher William; Hanks, Ruth E; Southern, Kevin W; Forton, Julian T; Thia, Lena P; Moat, Stuart J
Abstract : Objective: Wales has an immunoreactive trypsin (IRT)-DNA cystic fibrosis (CF) newborn screening (NBS) programme. Most CF NBS false negative cases are due to an IRT concentration below the screening threshold. The accuracy of IRT results is dependent on the quality of the dried bloodspot (DBS) sample. The aim of this study was to determine the cause of false negative cases in CF NBS and their relationship to DBS quality. Design: Longitudinal birth cohort. Setting: Wales 1996–2016. Patients: Children with CF. Interventions: Identification of all CF patients with triangulation of multiple data sources to detect false negative cases. Main outcome measures: False negative cases. Results: Over 20 years, 673 952 infants were screened and 239 were diagnosed with CF (incidence 1:2819). The sensitivity of the programme was 0.958, and positive predictive value was 0.476. Eighteen potential false negatives were identified, of whom eight were excluded: four screened outside Wales, two had complex comorbidities, no identified cystic fibrosis transmembrane conductance regulator (CFTR) variants on extended analysis and thus not considered to have CF and two were diagnosed after their 16th birthday. Of the 10 false negatives, 9 had a low DBS IRT and at least one common CFTR variant and thus should have received a sweat test under the programme. DBS cards were available for inspection for five of the nine false negative cases—all were classified as small/insufficient or poor quality. Conclusions: The majority of false negatives had a low bloodspot IRT, and this was associated with poor quality DBS. The optimal means to improve the sensitivity of our CF NBS programme would be to improve DBS sample quality.